Me, myself, and my muscles: associations between narcissism and muscle dysmorphia. Issue 1 (2nd January 2022) - Boulter, Matt W.; Sandgren, Sebastian S.
ABSTRACT: The conceptualisation and measurement of the associations between narcissism and muscle dysmorphia (MD) are poorly understood in the literature. It is recognised that narcissism features two broad dimensions: vulnerable and grandiose. Studying both narcissism dimensions is important given their differences in etiology and health-related outcomes. Therefore, the aim of this study was to investigate the associations between MD, vulnerable and grandiose narcissism. A total of 336 participants (48% male; M age = 26.4 years) completed measures of MD and narcissism. Hierarchical regression analysis revealed that vulnerable narcissism was significantly, positively associated with MD, whilst grandiose narcissism was not. Practitioners should be aware that vulnerable narcissism may be a potential risk factor of MD.